2016
DOI: 10.1128/jb.00366-16
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli P and Type 1 Pilus Assembly Chaperones PapD and FimC Are Monomeric in Solution

Abstract: The chaperone/usher pathway is used by Gram-negative bacteria to assemble adhesive surface structures known as pili or fimbriae. Uropathogenic strains of Escherichia coli use this pathway to assemble P and type 1 pili, which facilitate colonization of the kidney and bladder, respectively. Pilus assembly requires a periplasmic chaperone and outer membrane protein termed the usher. The chaperone allows folding of pilus subunits and escorts the subunits to the usher for polymerization into pili and secretion to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Furthermore, they can be up to 2 μm in length and 10 nm in width, which guarantees successful bacterial attachment. Meanwhile, numerous studies have found that over 50% of women with an acute UTI show strong positive type 1 fimbriae via the immunostaining of urine sediments [ 44 ], with results comparable to those obtained in acutely infected mice [ 45 ]. Interestingly, a study found that urine decreases the UPEC expression of type 1 fimbriae [ 46 , 47 ], which may explain the results above.…”
Section: Mechanisms Of Upec Utismentioning
confidence: 85%
“…Furthermore, they can be up to 2 μm in length and 10 nm in width, which guarantees successful bacterial attachment. Meanwhile, numerous studies have found that over 50% of women with an acute UTI show strong positive type 1 fimbriae via the immunostaining of urine sediments [ 44 ], with results comparable to those obtained in acutely infected mice [ 45 ]. Interestingly, a study found that urine decreases the UPEC expression of type 1 fimbriae [ 46 , 47 ], which may explain the results above.…”
Section: Mechanisms Of Upec Utismentioning
confidence: 85%
“…PAI IIJ96 contains a hly operon, as well as a prs operon encoding a different class of pilus and a gene encoding the cytotoxic necrotizing factor 1 (CNF1). [6][7][8] PAI ICFT073, which carries an Alpha-hemolysin operon (hly), a pap operon encoding P-fimbriae, aerobactin, and genes related to iron transport systems and putative carbohydrate transport systems. 9 PAI IICFT073 contains a pap operon, iron-regulated genes, mobile genetic elements, and a large number of unknown genes.…”
Section: Introductionmentioning
confidence: 99%
“… ( Walczak et al, 2014 ) FimC Chaperone donates its strand to upcoming pili during pili polymerization. ( Sarowar et al, 2016 ) FimD Usher pathway, transfers the pilin subunits from periplasm to outer membrane. ( Sarowar et al, 2016 ) FimF, G The adapter subunit, holds the pilin subunits.…”
Section: Pili In Gram-positive Bacteriamentioning
confidence: 99%
“… ( Sarowar et al, 2016 ) FimD Usher pathway, transfers the pilin subunits from periplasm to outer membrane. ( Sarowar et al, 2016 ) FimF, G The adapter subunit, holds the pilin subunits. ( Busch et al, 2015 ) FimH Tip pilin, mediates the host-pathogen interaction.…”
Section: Pili In Gram-positive Bacteriamentioning
confidence: 99%